Adsorption of Cd2+ onto apatite surface: Equilibrium, kinetics and thermodynamic studies - Edwin Andrew Ofudje; Ezekiel F. Sodiya; Olajire S. Olanrele; Fatai Akinwunmi (Heliyon, 2023)
This study examined the application of chemically synthesized apatite (CHAp) powder as a potential adsorbent for the elimination of Cd2+ in aqueous medium. The synthesized hydroxyapatite (HAp) powder before and after adsorption was elucidated by XRD, EDX, FT-IR, SEM, and TEM analytical techniques. The role of time, initial Cd2+ concentration, amount of CHAp used, temperature and solution pH on the adsorption process were investigated. Data from the adsorption process were subjected to Dubinin-Radushkevich, Langmuir, Freundlich, and Tempkin adsorption isotherms, while pseudo-first-order, pseudo-second-order, Elovich and intraparticle diffusion kinetic models were used for the kinetics investigation. Results from XRD confirmed that chief characteristic peaks of HAp powder were detected, while functional groups such as PO43−, CO32− and OH− matching pure HAp were displayed in the FT-IR spectra. Round shape morphology of the CHAp was confirmed by SEM and TEM analyses. Langmuir isotherm best described the adsorption process with ceiling adsorption capacity of 195.711 mg/g, whereas, the adsorption mechanism obeys the pseudo-first-order model which suggests a physical adsorption process. The value of entropy change (ΔS) of the adsorption of Cd2+ onto CHAp surface was obtained to be 0.610 kJ/mol, while the value of enthalpy change obtained was 175.591 kJ/mol. Results from free energy change obtained adjudged the adsorption process to be spontaneous and endothermic in character. Thus, the chemically synthesized HAp could be an excellent adsorbent for the elimination of Cd2+ in bioremediation applications.